Construction and application of a physically-based constitutive model for superplastic deformation of near-α TNW700 titanium alloy - Lixia Ma; Dingyong He; Bangjian Yang; Xiuquan Han; Jichun Zhang; Weidong Li (Journal of Materials Research and Technology)
The TNW700 alloy is designed for short-term service up to 700 °C to meet the high-temperature titanium alloy requirements for complex thin-walled cabin and rudder/wing components in high Mach aircraft. This study aims to develop a high-precision, physically-based unified viscoplastic constitutive model to predict superplastic deformation and microstructure evolution of TNW700 alloy conical components under complex loading. Firstly, damage characterization tests deepened the understanding of flow softening behavior and superplastic mechanism. The results indicate that voids primarily nucleate at α/β phase interfaces and triple junctions, gradually growing, elongating and coalescing into microcracks with increasing true strain. Then, a series of constitutive equations based on microstructure evolution (covering dislocation density, phase ratio, grain size and plastic damage) are established, accounting for the disparate deformation behavior of primary α and β phases. Material constants are calibrated using a genetic algorithm combined with multi-objective optimization. The proposed constitutive model exhibits high predictive accuracy, with an average absolute error of less than 14%, validated by comparisons with experimental phase ratios, grain sizes and flow stresses. The constitutive model is incorporated into the ABAQUS via the CREEP subroutine to validate its validity against the bulging test of conical parts. The bulging height, thickness and primary α grain size of the conical parts deformed at 950 °C exhibit good agreement between the FE-predicted and experimental results. Moreover, the bulging heights of the conical parts deformed at 910 °C and 930 °C further confirm the generalizability of the constitutive model.